Apología del reggaetón a los delitos (2021)
In this article aims to explain about the influence of reggaetón on the felonies, the malignant effects on the children, teenagers and adults, and the consequences of this malignant effects on the society. At the same time, this project wants to give an explication about the reason for not to consider this music how a cultural genre, so they content misogynist an allusive to illegal substances consume. Undermines the culture concept in a nation. This project also searches to find which the roll of the state to regulate the contents of reggaetón that can be find of a way too much that nobody can say that no listen reggaetón.